SANKSI KEBIRI DALAM KONTEKS KEJAHATAN SEKSUAL PADA ANAK: PERSPEKTIF HUKUM ISLAM DAN TEORI KEADILAN JOHN RAWLS - Mustafid, Mustafid; Sulastri, Sulastri; Qurtubi, Achmad Napis; Hosen, Hosen (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research aims to explore the views of Islamic law on the use of castration punishment in cases of sexual crimes against children and then relate it to the theory of justice put forward by John Rawls. This type of research is library research with a normative approach. Analysis was carried out using a qualitative descriptive approach. The results of this research are that there are two conditions. First, when the victim is the same as the perpetrator, this is called Liwath Sodomy and is punishable by death. Second, when the victim is not of the same type as the perpetrator, Zina is condemned; the sanction is for those who are married to be stoned to death and for those who are not married to be bound 100 times. Islam does not recognize the punishment of castration, so the law is ta'zir, but this does not mean that castration can punish perpetrators of sexual crimes against children. Furthermore, when related to John Rawls's theory of justice, first, the principle of equal standing emphasizes the importance of providing equal opportunities to all individuals, including criminals, to improve their social position. Second, the principle of equitable differences requires that inequality in society is only acceptable if it benefits the most disadvantaged. In the context of castration, the question is whether the action benefits the victim or society. Therefore, Jonh Rawls's concept of justice indirectly does not recognize the punishment of castration for sexual crimes against children.